2020
DOI: 10.1016/j.ergon.2020.102963
|View full text |Cite
|
Sign up to set email alerts
|

Applied anthropometry for common industrial settings design: Working and ideal manual handling heights

Abstract: Anthropometry has been used extensively for designing safe and sustainable products and workplaces. However, it is common that designers need straightforward guidelines and dimensions, which they often lack, for specific design situations. Anthropometric data are usually presented in tables that summarize percentile values, separated by gender, of a specific population, which makes it difficult for designers to generate applications for mixed populations, such as industrial settings. Using a recently collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…15 Consequently, anthropometric indexes can provide supportive information for designing of equipment. 16 In conclusion, our results showed that there is a statistically significant correlation among stature, forearm, and hand length for students of Hamadan University of Medical Sciences. Furthermore, the forearm length is a more predictive factor than hand length in stature estimation.…”
Section: Discussionmentioning
confidence: 50%
“…15 Consequently, anthropometric indexes can provide supportive information for designing of equipment. 16 In conclusion, our results showed that there is a statistically significant correlation among stature, forearm, and hand length for students of Hamadan University of Medical Sciences. Furthermore, the forearm length is a more predictive factor than hand length in stature estimation.…”
Section: Discussionmentioning
confidence: 50%
“…Perbaikan desain kursi pernah dilakukan, dalam penelitiannya menggunakan data antropometri untuk menentukan kisaran ketinggian, kedalaman, dan sudut sandaran [22]. Menerapkan antropometri ke dalam desain dapat membantu meningkatkan produktivitas dan efisiensi [23]. Adapun beberapa rumus pengujian yang dilakukan dalam penenelitian ini sebagai berikut:…”
Section: Antropometriunclassified
“…The recent literature has extensively explored women’s anthropometry in the context of minimizing adverse occupational health outcomes. Studies such as [ 16 ] have focused on addressing the mismatch of workplace height for manual handling, utilizing female anthropometric measures to reduce musculoskeletal disorders. The design of manual tools for various occupations, including farming [ 17 ], hand looming [ 18 ], dentistry [ 19 ], and packaging [ 20 ], has integrated women’s anthropometry to mitigate fatigue and biomechanical stresses.…”
Section: Introductionmentioning
confidence: 99%